Gestión administrativa financiera y su incidencia en la rentabilidad de productos agrícolas de la empresa Comcabsa, cantón Ventanas período 2013-2014, plan de capacitación. - Franco Litardo, Fátima del Rocío (2015)
This research was conducted in order to evaluate the effect of administrative financial management in the profitability of agricultural goods COMCABSA, Ventanas canton 2013-2014. To achieve this goal the management of financial, material, technological and human are analyzed, administrative procedures and strategies to implement internal activities are also investigated, the level of profitability obtained by each agricultural product is determined, the same as allowed design an operating plan to improve efficiency, effectiveness and economy of the company, in order to propose alternatives for improvement, to guide managers of the company to promote a suitable organizational culture and obtain favorable results. In this investigation, we interviewed the President and General Manager of the company COMCABSA, employee surveys of the same were also performed. sources were consulted as: brochures, letters, books, internal policies, and the Internet. For data processing the SPSS 17.0 software was used, then the results where it was accepted or rejected the hypothesis is analyzed. The most important challenge of the research is to make COMCABSA have a high degree of reliability of the administration for the management of economic, technological and human materials, thereby obtaining an adequate return. The results showed that the company employs management strategies such as: the financial risk with banks and suppliers, competitive pricing, product quality, technology, skilled labor, among others, but require other special staff training, coding inventories and training plan to improve operational management, COMCABSA has a low level of efficiency and effectiveness due to the absence of a document where the administrative, financial and marketing strategies are demonstrated, along with weak planning by operating activities and administration. Which markets and bring the company to profitability they are cocoa, corn and coffee produce.